EFFICACY OF CHANDRAPRABHA VATI WITH GLIMEPIRIDE IN NEWLY DIAGNOSED TYPE 2 DIABETES PATIENTS: A RANDOMIZED CLINICAL TRIAL - AHALYA SP; VIJAYAKUMAR TM; SATISH KUMAR RC (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of the study was to evaluate the therapeutic potential of Chandraprabha Vati with glimepiride as an add-on therapy in newly diagnosed diabetes mellitus (DM) patients. Methods: A 6-month, open-label, randomized clinical trial was conducted on 60 newly diagnosed Type 2 DM (T2DM) patients. Participants were divided into two groups: Group 1 received glimepiride 1 mg daily, and Group 2 received glimepiride 1 mg plus chandraprabha vati 250 mg daily. Glycemic parameters (fasting blood sugar [FBS], postprandial blood sugar [PPBS], glycated hemoglobin [HbA1c]) were measured at baseline, 12 weeks, and 24 weeks. Results: Group 2 showed significant reductions in FBS, PPBS, and HbA1c compared to Group 1 at both 12 and 24 weeks. Conclusion: In this study, chandraprabha vati as an adjunct to glimepiride significantly improves glycemic control in newly diagnosed T2DM patients. These findings support the integration of Ayurvedic for diabetes management but careful monitoring is required since the plant compounds may cause adverse reactions in some people with less tolerance.